Case Report: Rubella Virus-Induced Cutaneous Granulomas in Two Pediatric Patients With DNA Double Strand Breakage Repair Disorders – Outcome After Hematopoietic Stem Cell Transplantation - Baumann, Ulrich; Schulte, Johannes H.; Groß, Jonathan P.; Beier, Rita; Ludwig, Marius; Wahn, Volker; Hofmann, Jörg; Maecker-Kolhoff, Britta; Sauer, Martin; Kaiser-Labusch, Petra; Karimian, Negin; Blume-Peytavi, Ulrike; et al. (Frontiers in Immunology, 2022)
We report two patients with DNA repair disorders (Artemis deficiency, Ataxia telangiectasia) with destructive rubella virus-induced skin granulomas, presumably triggered by live-attenuated rubella vaccinations. Rapid resolution of skin lesions was observed following hematopoietic stem cell transplantation. However, the patient with AT died due to complications of severe hepatic veno-occlusive disease 6 month after HSCT. Newborn screening may help to prevent patients with moderate T-cell deficiency from receiving live-attenuated rubella vaccine potentially causing granulomas.